Guided Brillouin interactions - from optical vortex isolators to extreme thermodynamics - Stiller, Birgit (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Brillouin-Mandelstam scattering is the strongest optomechanical effect in waveguides and optical fibers. It gives access to the domain of acoustic waves which follow other guiding rules and are sensitive to different parameters of the material such as pressure or temperature. This opens the opportunity to - on the one hand - modulate and process optical signals via mechanical vibrations which can be shaped by the design and material of the optoacoustic waveguides and - on the other hand - gain an insight into material properties and environmental changes. In this talk, experimental results on two topics will be presented.
CRIS-Team Scopus Importer:2024-12-16